Medicinal and edible composite particle capable of relieving liver injury, preparation method and application

By loading phosphorylated zein-chitosan oligosaccharide particles with puerarin, an efficient delivery system with hydrophilic exterior and hydrophobic interior was constructed, which solved the solubility and stability problems of puerarin in the body, achieved the multi-target protection and sustained release effect of puerarin in alcoholic liver injury, and improved its therapeutic effect.

CN120713889APending Publication Date: 2025-09-30YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510790776.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

In actual applications, puerarin faces problems such as poor water solubility, low intestinal absorption rate and insufficient chemical stability, which makes it difficult to achieve ideal therapeutic concentration and duration of action in the body, limiting its effectiveness in the treatment of alcoholic liver injury.

Method used

Composite particles of phosphorylated zein-chitosan oligosaccharide particles loaded with puerarin are used to improve the bioaccessibility and stability of puerarin by constructing an efficient delivery system with hydrophilic exterior and hydrophobic interior. Combined with the liver protective effect of chitosan oligosaccharide, multi-target protection is achieved.

Benefits of technology

It significantly improves the drug loading capacity and bioaccessibility of puerarin, prolongs its circulation time in the body, enhances its medicinal effect, and shows significant alcohol-relieving and liver-protecting effects in alcoholic liver damage, which has economic and social value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120713889A_ABST
    Figure CN120713889A_ABST
Patent Text Reader

Abstract

The invention discloses a medicinal and edible composite particle capable of relieving liver injury and a preparation method and application thereof.The particle is a puerarin-loaded phosphorylated hollow zein-chitosan oligosaccharide particle and has an efficient delivery structure with the exterior hydrophilic and the interior hydrophobic, the bioavailability is improved while the puerarin drug loading capacity is increased, and the bioavailability is improved. The circulation time in the body is prolonged, and the medicinal effect is enhanced. Meanwhile, the chitosan oligosaccharide in the components of the composite particle has a liver protection effect and can be cooperated with the anti-oxidation and anti-alcohol characteristics of puerarin, so that multi-target protection in alcoholic liver injury is realized, and the composite particle can be used for expanding and developing treatment medicines or health-care foods with anti-alcohol and liver-protecting effects and has remarkable economic and social values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a preparation, and in particular to a medicine-food composite particle capable of alleviating liver damage, a preparation method and an application thereof. Background Art

[0002] Alcoholic liver disease (ALD) is a serious condition characterized by progressive damage to liver structure and function caused by long-term excessive alcohol consumption. It is not a single condition but rather a continuum of pathological changes encompassing alcoholic fatty liver disease, alcoholic hepatitis, liver fibrosis, cirrhosis, and ultimately liver cancer. ALD imposes a significant health burden worldwide and is a major cause of liver disease-related mortality. Its root cause lies in the direct toxicity of alcohol and its metabolites on hepatocytes, triggering complex pathological processes such as inflammation and oxidative stress.

[0003] Among the many natural substances with the potential to soothe hangovers and protect the liver, puerarin (Pur) has garnered widespread attention due to its remarkable effects. Puerarin is a major active isoflavone compound isolated from the traditional Chinese medicine Pueraria root. Studies have shown that it has clear alcohol soothing and liver-protecting effects, is relatively low-cost, and has minimal adverse reactions, demonstrating promising application prospects.

[0004] However, puerarin faces significant technical bottlenecks in its practical application, severely restricting its full potential. The core issue lies in its poor physicochemical properties: poor water solubility hinders dissolution and distribution in the body; low intestinal absorption results in low oral bioavailability; and insufficient chemical stability affects its effectiveness and durability during processing, storage, and in vivo environments. These deficiencies make it difficult to achieve the ideal therapeutic concentration and duration of action in the body, even with its excellent activity. Summary of the Invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a medicinal and edible composite particle that improves the water solubility, intestinal absorption rate and stability of puerarin and can alleviate liver damage; the second purpose is to provide a method for preparing the medicinal and edible composite particle; the third purpose is to provide applications of the medicinal and edible composite particle.

[0006] Technical solution: The medicine-food composite particles of the present invention are phosphorylated zein-chitosan oligosaccharide particles loaded with puerarin, wherein the mass ratio of puerarin, zein, and chitosan oligosaccharide is 1:5:2-13.

[0007] Preferably, the chitosan oligosaccharide is an oligosaccharide with a degree of polymerization of 2-20.

[0008] The method for preparing the medicinal and edible composite particles of the present invention comprises the following steps:

[0009] (1) Add puerarin at a final concentration of 5-15 mg / mL to a 4-6% zein-ethanol solution and mix;

[0010] (2) adding 0.5-1.5 times the volume of the solution obtained in step 1 with a 0.1-0.5% sodium carbonate-ethanol solution by mass volume fraction and mixing;

[0011] (3) adding 3-5 times the volume of anti-solvent to the solution obtained in step 2 and mixing;

[0012] (4) removing ethanol from the solution obtained in step 3 by distillation under reduced pressure, and using an anti-solvent to make up the evaporation volume;

[0013] (5) adding 3-5 times the volume of 0.1-2 mg / mL sodium tripolyphosphate solution to the solution obtained in step 4 and mixing the mixture;

[0014] (6) adding chitosan oligosaccharide (0.2-5 times the amount of zein) to the solution obtained in step 5 and mixing;

[0015] (7) The solution obtained in step 6 is dialyzed and freeze-dried to obtain medicinal and edible composite particles.

[0016] Preferably, the zein-ethanol solution in step 1 has an ethanol concentration of 60-80%.

[0017] Preferably, the sodium carbonate-ethanol solution in step 2 is prepared by adding 1.5-4 times the volume of anhydrous ethanol to a sodium carbonate aqueous solution having a mass volume fraction of 1%, and mixing; the final concentration of ethanol is 60-80%.

[0018] Preferably, the anti-solvent in step 3 is any one of deionized water, double distilled water, and ultrapure water.

[0019] Preferably, the reduced pressure distillation in step 4 is performed by heating to 35-40° C. and rotary evaporation.

[0020] Preferably, the chitosan oligosaccharide in step 6 is an oligosaccharide with a degree of polymerization of 2-20.

[0021] Preferably, the dialysis step in step 7 is performed at 2-8° C. with a molecular weight cut-off of 30-40 kDa MWCO.

[0022] The invention relates to an application of the medicine-food composite particles in the preparation of a medicine for treating alcoholic liver damage.

[0023] The invention discloses an application of the medicine-food composite particles in the preparation of health-care food for alleviating alcoholic liver damage.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. By constructing a composite particle of phosphorylated hollow zein and chitosan oligosaccharide loaded with puerarin, a highly efficient delivery system with external hydrophilicity and internal hydrophobicity is formed, which increases the drug loading of puerarin while also improving its bioaccessibility, prolonging its circulation time in the body and enhancing its medicinal effect; (2) The liver protective effect of chitosan oligosaccharide can cooperate with the antioxidant and alcohol-detoxifying properties of puerarin to achieve multi-target protection in alcoholic liver damage, which can expand the development of therapeutic drugs or health foods with alcohol-detoxifying and liver-protecting effects, and has significant economic and social value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The graph shows the particle size and potential measurement results of phosphorylated hollow zein nanoparticles with different puerarin loadings and different chitosan oligosaccharide complexes;

[0026] Figure 2 Transmission electron microscopy results of phosphorylated hollow zein nanoparticles with different puerarin loadings and different chitosan oligosaccharide complexes;

[0027] Figure 3 The figure shows the results of the encapsulation efficiency and loading rate determination of phosphorylated hollow zein nanoparticles with different puerarin loadings and different chitosan oligosaccharide complexes;

[0028] Figure 4 The figure shows the thermal stability test results of phosphorylated hollow zein nanoparticles with different puerarin loadings and different chitosan oligosaccharide complexes;

[0029] Figure 5 The figure shows the release rate measurement results of phosphorylated hollow zein nanoparticles with different puerarin loadings and different chitosan oligosaccharide complexes;

[0030] Figure 6 The results of HE staining of liver tissue pathological sections of mice in different treatment groups;

[0031] Figure 7 The results of serum alanine aminotransferase and aspartate aminotransferase assays in mice in different treatment groups are shown in the figure;

[0032] Figure 8 The graph shows the results of serum alcohol dehydrogenase and acetaldehyde dehydrogenase determination in mice in different treatment groups. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described below.

[0034] Example 1: Preparation of medicinal and edible composite granules and control composite granules

[0035] 1. Preparation of phosphorylated zein nanoparticles

[0036] (1) A 1% (w / v) sodium carbonate aqueous solution and anhydrous ethanol were mixed in a volume ratio of 3:7 to obtain a sodium carbonate template solution;

[0037] (2) Add an equal volume of sodium carbonate template solution to a 5% (w / v) zein-ethanol solution and mix under magnetic stirring at 1000 rpm for 5 min;

[0038] (3) Add 4 times the volume of ultrapure water to the mixed solution, mix and magnetically stir at 1000 rpm for 10 min;

[0039] (4) The obtained solution was subjected to rotary evaporation at 38° C. to remove ethanol from the system, and ultrapure water was added to make up the evaporation volume to obtain a hollow zein particle solution;

[0040] (5) Take 10 mL of the hollow zein particle solution, add 40 mL of 1.25 mg / mL sodium tripolyphosphate solution, and stir magnetically at 1000 rpm for 30 min to fully carry out the phosphorylation reaction;

[0041] (6) After the reaction, 10, 25, and 50 mg of chitosan oligosaccharide (COS) were added and magnetically stirred at 40°C for 45 min to allow COS to fully combine with the particles to form composite particles, where 10 mg was added as L, 25 mg as M, and 50 mg as H;

[0042] (7) The resulting solution was placed in a dialysis bag with a molecular weight cutoff of 35 kDa and dialyzed with deionized water at 4°C for 72 h.

[0043] (8) After dialysis, freeze-drying was performed for 72 h to obtain phosphorylated zein nanoparticles (Uncapsulation PHZn) or acidified zein nanoparticles complexed with chitosan oligosaccharides at different ratios (Uncapsulation PHZn-COSL, Uncapsulation PHZn-COSM, Uncapsulation PHZn-COSH).

[0044] 2. Preparation of Puerarin-Loaded Phosphorylated Zein Nanoparticles

[0045] (1) A 1% (w / v) sodium carbonate aqueous solution and anhydrous ethanol were mixed in a volume ratio of 3:7 to obtain a sodium carbonate template solution;

[0046] (2) Puerarin at a final concentration of 1% (w / v) was added to a 5% (w / v) zein-ethanol solution and magnetically stirred at 1000 rpm for 15 min. Then, an equal volume of sodium carbonate template solution was added to the resulting solution and magnetically stirred at 1000 rpm for 5 min.

[0047] (3) Add 4 times the volume of ultrapure water to the mixed solution, mix and magnetically stir at 1000 rpm for 10 min;

[0048] (4) The resulting solution was subjected to rotary evaporation at 38° C. to remove ethanol from the system, and ultrapure water was added to make up the evaporation volume to obtain a zein particle solution loaded with puerarin;

[0049] (5) Take 10 mL of the hollow zein particle solution, add 40 mL of 1.25 mg / mL sodium tripolyphosphate solution, and stir magnetically at 1000 rpm for 30 min to fully carry out the phosphorylation reaction;

[0050] (6) After the reaction, 10, 25, and 50 mg of chitosan oligosaccharide (COS) were added and magnetically stirred at 40°C for 45 min to allow COS to fully combine with the particles to form composite particles, where 10 mg was added as L, 25 mg as M, and 50 mg as H;

[0051] (7) The resulting solution was placed in a dialysis bag with a molecular weight cutoff of 35 kDa and dialyzed with deionized water at 4°C for 72 h.

[0052] (8) After dialysis, freeze-drying for 72 h was performed to obtain phosphorylated zein nanoparticles loaded with puerarin (Encapsulation PHZn), or edible and medicinal composite particles, i.e., acidified zein nanoparticles loaded with puerarin and chitosan oligosaccharide (Encapsulation PHZn-COSL, Encapsulation PHZn-COSM, Encapsulation PHZn-COSH).

[0053] Example 2: Characterization of composite particles

[0054] 1. Particle yield

[0055] The particle yield of the nanoparticles prepared in Example 1 was calculated according to the following formula:

[0056]

[0057] Wherein, M1 is the total mass of all substances added in the process of preparing composite particles; M2 is the mass of composite particle powder obtained after freeze-drying, both in g.

[0058] The particle yield results are shown in Table 1:

[0059] Table 1 Calculation results of particle yield

[0060]

[0061]

[0062] Statistical results showed that the particle yields of phosphorylated hollow zein nanoparticles before and after puerarin loading were 71.33% and 70.91%, respectively, without significant differences. With increasing COS loading, the particle yields of phosphorylated hollow zein nanoparticles before and after puerarin loading increased significantly to 88.22% and 85.54%, respectively. At the same COS loading level, except for the intermediate COS loading level, there was no significant difference in the particle yields of the composite particles before and after puerarin loading. This difference may be due to experimental error. This indicates that the addition of COS further improves the preparation efficiency of the composite particles.

[0063] 2. Particle size and potential

[0064] 1.5 mL of the dialyzed particle solution from Example 1 was added to a quartz cuvette and particle size analysis was performed using a laser particle size analyzer at 25°C. Zeta potential was measured by placing the sample into a potential cell. The number of independent runs was set to 13 before measurement.

[0065] The results are as follows Figure 1 As shown, Figure 1 A is the particle size measurement result. As the COS addition amount continues to increase, the particle size of PHZn before and after loading increases from the initial 169.7nm and 193.2nm to 206.7nm and 262.1nm, respectively. This is because PHZn and COS have opposite surface charges, and the two can bind through electrostatic interactions, forming a polysaccharide coating composed of COS molecules on the particle surface. At the same COS addition amount, the particle size of the composite particles increases by 20-60nm after loading with puerarin. This indicates that puerarin enters the cavity of the hollow particles, increasing the particle volume. At the same time, the filling of puerarin causes the particles to deform or expand, resulting in an increase in particle size.

[0066] Figure 1 B is the Zeta potential measurement result. The Zeta potential of PHZn is -42.46 mV. When low, medium and high levels of COS are added, the Zeta potential increases to -35.13 mV, -33.00 mV and -29.30 mV, respectively, all higher than 25 mV, indicating that the formed composite particles have good stability in the dispersed system. At the same time, at the same COS addition amount, the absolute value of the Zeta potential of the composite particles loaded with puerarin is higher than that of the unloaded particles, which may be due to the interaction between the polar groups of puerarin and zein, which leads to an increase in the surface charge density of the particles, thereby increasing the absolute value of the Zeta potential.

[0067] 3. Microscopic morphology

[0068] The freeze-dried sample was reconstituted with ultrapure water to obtain a reconstituted solution with a concentration of 0.1-0.5% (w / v). 100 μL of the reconstituted solution was added dropwise to a copper mesh and air-dried at room temperature. The sample was negatively stained with 1% phosphotungstic acid solution and dried under an incandescent lamp. The micromorphological characteristics of the sample were observed using a transmission electron microscope at an accelerating voltage of 100 kV.

[0069] The results are as follows Figure 2 As shown, Figure 2 A is PHZn, Figure 2 B is PHZn-COSH, Figure 2 C is PHZn-COSH-puerarin, and the individual particles of all test samples present a spherical structure: compared with PHZn, an obvious COS coating layer appears on the outside of the composite particles after the addition of COS; and after loading puerarin, the bright area inside the original hollow particles disappears, which also indicates the successful loading of puerarin.

[0070] Example 3: Performance evaluation of medicinal and edible composite granules

[0071] 1. Solubility

[0072] The lyophilized powder obtained in Example 1 was prepared into a 0.5 mg / mL solution using ultrapure water. The solution was centrifuged at 12,000 rpm for 3 minutes at room temperature. The supernatant was assayed using a BCA protein concentration kit to calculate the dissolved protein concentration. Native zein was used as a control. Protein solubility was calculated according to the following formula:

[0073]

[0074] Wherein, C1 is the measured supernatant protein concentration, and C0 is the concentration of the diluted protein sample: 0.5 mg / mL.

[0075] The solubility results are shown in Table 2:

[0076] Table 2 Solubility calculation results

[0077] Sample name Unloaded puerarin Loaded with puerarin PHZn 44.59±2.28% 45.26±3.17% PHZn-COSL 62.80±4.50% 62.42±4.31% PHZn-COSM 69.92±3.24% 70.88±2.45% PHZn-COSH 76.38±1.44% 76.29±1.40%

[0078] The solubility results showed that the addition of COS could further significantly improve the solubility of PHZn, and with the continuous increase of COS addition, the solubility also gradually increased, reaching a maximum of 76.38%.

[0079] 2. Encapsulation rate and loading rate

[0080] The puerarin-loaded sample after dialysis in Example 1 was centrifuged at 2000 rpm for 20 min to remove free puerarin. 300 μL of the supernatant was added to 700 μL of anhydrous ethanol and diluted 50-fold with 70% ethanol. The absorbance at 250 nm was measured. The absorbance at 250 nm of the unloaded particle sample dilution with the same concentration and dilution factor was used as the background value. After deducting the background value, the absorbance value obtained was substituted into the puerarin standard curve: y = 0.1123x + 0.0206 (R 2 =0.9990) to calculate the successfully encapsulated puerarin content. Where y represents the absorbance value and x represents the puerarin concentration (μg / mL). The encapsulation efficiency (EE) and loading rate (LC) of puerarin were calculated according to the following formula:

[0081]

[0082] Among them, M0 is the total content of zein nanoparticles; M1 is the total content of puerarin; M2 is the total content of successfully encapsulated puerarin, and the above units are all mg.

[0083] The results are as follows Figure 3 As shown in Figure 2, with the continuous addition of COS, the encapsulation efficiency of the particles increased from 77.57% (PHZn) to 92.55% (PHZn-COSH), and the corresponding loading rate also increased from 15.51% (PHZn) to 18.51%.

[0084] It can be seen that the addition of COS significantly improved the encapsulation efficiency and loading rate of zein, and this improvement became more obvious with the increase in the amount of COS added. PHZn-COSH showed the highest encapsulation efficiency and loading rate, and was the optimal ratio.

[0085] 3. Thermal stability

[0086] The dialyzed particle solution in Example 1 was heated in a water bath at 50°C, 60°C, 70°C and 80°C for 1 h, and then refrigerated at 4°C overnight to measure the particle size. The particle size was used to reflect the thermal stability of the composite particles.

[0087] The results are as follows Figure 4 As shown, from Figure 4As can be seen in A, in the particles without puerarin loading, the range of change in the particle size of all sample particles is small as the temperature increases, indicating that PHZn itself has good thermal stability; and when no COS is added, the particle size of PHZn increases from 194.7nm at 50℃ to 208.6nm at 80℃, with an increase of 13.7nm; and this increase is 9.9nm, 7.3nm, and 9.4nm at low, medium, and high levels of COS addition, respectively, which are all smaller than those without COS addition, indicating that the addition of COS improves the thermal stability of the composite particles.

[0088] from Figure 4 As can be seen in Figure B, the particle size of the puerarin-loaded composite particles changes more significantly under different temperature conditions than that of the unloaded particles, indicating that the loading process may have affected the thermal stability of the particles. Without the addition of COS, the particle size of the PHZn-puerarin increased from 187.7 nm at 50°C to 224.1 nm at 80°C, an increase of 36.4 nm. This increase was 31.6 nm, 30.8 nm, and 11.2 nm at low, medium, and high levels of COS addition, respectively. The addition of COS, especially at high levels, significantly improved the thermal stability of the puerarin-loaded composite particles, indicating that the addition of COS can effectively improve the thermal stability of the loaded particles.

[0089] 4. Release rate

[0090] A static digestion model consisting of oral, gastric, and small intestinal phases was used to evaluate the in vitro digestibility of the composite particles.

[0091] The freeze-dried puerarin-loaded phosphorylated zein nanoparticles and puerarin from Example 1 were weighed and prepared into 10 mg / mL dispersions with ultrapure water. The puerarin content was calculated based on the encapsulation efficiency. 10 mL of the composite particle dispersion was placed into a 20 kDa MWCO dialysis bag, which was then placed in a beaker containing ultrapure water. The beaker was then placed in a 37°C constant-temperature water bath in an oscillator to simulate the human digestive process. The specific digestion process was as follows:

[0092] (1) Oral phase, 0-10 minutes

[0093] Prepare 10 mL of simulated saliva fluid (SSF) and incubate at 37°C for 10 minutes. Once digestion begins, add it to the dialysis bag and mix with the sample. Adjust the pH of the system to 6.8 and oscillate at 100 rpm. After 10 minutes, sample the release medium outside the dialysis bag for puerarin content.

[0094] (2) Gastric phase, 11-70 minutes

[0095] Prepare simulated gastric fluid (SGF) in advance: Place 0.2g NaCl, 0.32g pepsin, and 700μL hydrochloric acid in a volumetric flask and dilute to 100mL with ultrapure water. Incubate 10mL of SGF at 37°C for 10 minutes. After the simulated oral digestion is complete, add it to the dialysis bag. Adjust the pH of the system to 2.5 and oscillate at 100rpm. Samples of the release medium outside the dialysis bag are collected at 40 and 70 minutes for determination of puerarin content.

[0096] (3) Small intestine phase, 71-190 minutes

[0097] Prepare simulated intestinal fluid (SIF) in advance: Place 0.68 g of potassium dihydrogen phosphate and 1 g of trypsin in a volumetric flask and dilute to 100 mL with ultrapure water. Incubate 10 mL of SIF at 37°C for 10 minutes. After the simulated gastric digestion is complete, add it to the dialysis bag. Adjust the pH of the system to 6.8 and oscillate at 100 rpm. Samples of the release medium outside the dialysis bag are collected at 100, 130, 160, and 190 minutes for determination of puerarin content.

[0098] The released puerarin content was calculated according to the method in Experiment 2 above. The in vitro puerarin release rate (Release rate) of the composite particles was calculated according to the puerarin content measured at different time points according to the following formula:

[0099]

[0100] Wherein, M0 is the initial puerarin content in the composite particles; M1 is the puerarin content measured by sampling in the release medium at different time points, and the above units are all mg.

[0101] The results are as follows Figure 5 As shown in the figure, in the oral phase, the in vitro release rate of puerarin not loaded by particles was the largest, reaching 21.41%, while the release rate of puerarin loaded by particles in the oral phase was significantly reduced, ranging from 10% to 20%.

[0102] After 1 hour of simulated digestion in the gastric phase, the total release rate of unloaded puerarin was 45.53%. However, the in vitro release rate of puerarin loaded with particles in the gastric phase was significantly reduced, with release rates of 36.90% (PHZn), 30.91% (PHZn-COSL), 27.97% (PHZn-COSM), and 25.02% (PHZn-COSH), respectively. This indicates that the loading of particles reduces the release of puerarin in the stomach to a certain extent, reducing the burst release of the drug in the acidic environment.

[0103] After entering the small intestine, puerarin in each group was further released. The in vitro release rate of unloaded puerarin reached 74.75% at 100 minutes and approached 90% at 200 minutes. In contrast, the release rate of puerarin slowed down and the cumulative release rate decreased after PHZn loading, with only 76.18% cumulatively released at 190 minutes. After compounding with COS, this value further decreased to 63.00% (PHZn-COSL), 57.24% (PHZn-COSM), and 52.67% (PHZn-COSH), respectively. This shows that the loading of PHZn and the addition of COS can control the slow and continuous release of puerarin in the small intestine, to a certain extent improving the stability of the drug, thereby prolonging the drug's duration of action and enhancing its bioavailability.

[0104] Among all the samples, PHZn-COSH performed best in simulated digestion, with cumulative release rates of 10.39%, 35.40% and 52.67% after digestion in the oral, gastric and small intestinal phases, respectively. This indicates that it can not only reduce the rapid release of puerarin in the initial stage, but also enable puerarin to be released more stably and continuously throughout the digestion process, showing excellent sustained-release properties.

[0105] In summary, the medicinal and edible composite particles can effectively regulate the release behavior of puerarin through the loading of PHZn and the compounding of COS, reduce its sudden release in the stomach, and achieve its slow and sustained release in the small intestine, which is of great value for improving the stability and bioavailability of puerarin.

[0106] 6. O2 - Free radical scavenging rate

[0107] Determination of O2 in composite particles by pyrogallol autoxidation method - Free radical scavenging rate (·O2 - scavenging activity).

[0108] Mix 0.1mol / L Tris solution with 0.1mol / L hydrochloric acid solution to prepare a 50mmol / L Tris-hydrochloric acid solution. Then take 1mL of the dialyzed particles in Example 1 and mix it with an equal volume of Tris-hydrochloric acid solution. After water bathing at 25°C for 30 minutes, immediately add 0.1mL of 3mmol / L pyrogallol solution and start timing. Measure the absorbance at 325nm every 30 seconds for 5 minutes. After the measurement is completed, calculate the slope K with time as the horizontal axis and absorbance as the vertical axis. Replace the sample with an equal volume of ultrapure water and repeat the above operation as a blank control. ·O2 - The free radical scavenging rate is calculated as follows:

[0109]

[0110] Among them, K s is the calculated sample slope, K c is the ultrapure water control slope.

[0111] O2 - The free radical scavenging rate results are shown in Table 3:

[0112] Table 3 O2 - Calculation results of free radical scavenging rate

[0113]

[0114]

[0115] O2 - The results of free radical scavenging rate showed that PHZn·O2 - The free radical scavenging ability of PHZn was significantly improved with the COS compound treatment in both the state without puerarin loading and the state with puerarin loading (p < 0.05). - The free radical scavenging rate was the lowest, only 4.17%; while PHZn-COSH's·O2 - The free radical scavenging rate was the highest, reaching about 42.67%. When the composite particles were loaded with puerarin, the·O2 - The free radical scavenging rates of COS and puerarin were significantly improved (p < 0.05), among which PHZn-COSH performed the best, with a scavenging rate of 79.44%, which showed that COS and puerarin both had good O2 - Free radical scavenging ability, and the two can synergistically show good antioxidant effects.

[0116] Example 4: In vivo evaluation of the effects of medicinal and edible composite granules

[0117] SPF-grade ICR mice were housed in individually ventilated cages. The room temperature was maintained at 24±2°C during the experiment. All mice had free access to food and water. The mice were randomly divided into: blank control group (Control group), model control group (Model group), silybin positive control group (Silybin group), puerarin group (Puerarin group), uncapsulated particles group (Uncapsulated particles group), high-dose encapsulated particles group (Encapsulated particles (HD) group), medium-dose encapsulated particles group (Encapsulated particles (MD) group), and low-dose encapsulated particles group (Encapsulated particles (LD) group). Each group had 2 cages, with 6 mice in each cage. After numbering and marking, the mice were adaptively raised for one week, and the experiment officially began on the 8th day.

[0118] Before the formal experiment began, the test samples were prepared. The test samples and dosages of each group are shown in Table 4:

[0119] Table 4 Test samples and doses in different groups in the acute alcoholic liver injury experiment in mice

[0120] Serial number Group Test samples dose 1 Blank control group Normal saline \ 2 Model control group Normal saline \ 3 Positive control group Silybin 100mg / kg.bw 4 Puerarin group Puerarin 150mg / kg.bw 5 Unloaded particle group PHZn-COSH 800mg / kg.bw 6 High-dose loaded particle group PHZn-COSH-puerarin 150mg puerarin / kg.bw 7 Medium-dose group of loaded particles PHZn-COSH-puerarin 100mg puerarin / kg.bw 8 Low-dose loaded particle group PHZn-COSH-puerarin 50mg puerarin / kg.bw

[0121] The test sample of the positive control group was an aqueous solution prepared with silybin; the test sample of the puerarin group was a puerarin dispersion prepared by dispersing puerarin in pure water and stirring uniformly; the test sample of the unloaded particle group was a composite particle solution prepared with pure water according to the concentration of composite particles in the test sample solution of the high-dose particle-loaded group using the lyophilized powder of Uncapsulation PHZn-COSH prepared in Example 1; the test samples of the high-, medium-, and low-dose particle-loaded groups were all the lyophilized powder of Encapsulation PHZn-COSH prepared in Example 1, and then composite particle solutions with different puerarin concentrations were prepared with pure water based on the loading rate result (18.72%).

[0122] Each cage of mice was first gavaged with the test sample. The timer started immediately after the gavage. After 30 minutes, the mice were gavaged with edible alcohol at a concentration of 55% alcohol and a dose of 10 mL / kg.bw. The above steps were repeated for 7 consecutive days.

[0123] On the 7th day after gavage, the mice were fasted for 24 h but not water. Blood was collected from the ocular vein of the mice and centrifuged at 3000 rpm at 4°C to obtain serum. The activities of serum aspartate aminotransferase and alanine aminotransferase, and the activities of alcohol dehydrogenase and acetaldehyde dehydrogenase in liver tissue were determined using commercially available kits.

[0124] Immediately after blood collection, the mouse liver was taken out, washed with physiological saline and dried with filter paper, weighed and then divided into two parts. One half was frozen for later use, and the other half was immersed in 4% tissue cell fixative, dehydrated, embedded, sectioned, and then stained with HE for pathological analysis.

[0125] Liver histopathological sections of mice in different groups Figure 6 As shown, the liver tissue structure of the blank control group mice was intact, the hepatic lobules were clearly arranged, the hepatocytes had regular morphology, the nucleoli were visible, and there were no signs of degeneration or necrosis. In contrast, the liver tissue structure of the mice in the model control group was variable, the hepatic lobules were disordered, the hepatocytes were irregularly arranged, and there was obvious fatty degeneration and cell swelling, which are typical characteristics of acute alcoholic liver injury. Under the intervention of different samples, there were significant differences in the morphology of liver tissue. After intervention in the particle-loaded group, the hepatocytes became round and plump again and arranged regularly, with no obvious abnormalities. The results of mouse liver tissue pathological sections also demonstrated the good effectiveness of the composite particles in sobering up and protecting the liver, and there is potential for further development into functional foods or drugs for sobering up and protecting the liver.

[0126] The results of serum index detection of mice in different groups are as follows Figure 7-8 As shown in the acute alcoholic liver injury model, the effects of different test samples on ALT activity in mouse serum are as follows Figure 7 As shown in Figure A, the ALT activity of the model control mice increased significantly, reaching approximately 149.7 U / L, far higher than the 38.9 U / L in the blank control group. This indicates that the large amount of alcohol ingested by the mice caused significant liver cell damage, resulting in the release of ALT into the serum. Both silybin and puerarin treatment significantly reduced ALT activity, to 56.8 U / L and approximately 106.1 U / L, respectively, demonstrating their protective effects against alcoholic liver injury. The ALT activity of the unloaded particle group was 115.9 U / L, while in the particle-loaded group, the ALT activity of the high-dose, medium-dose, and low-dose groups decreased to approximately 62.7 U / L, 90.1 U / L, and 121.3 U / L, respectively, significantly lower than that of the model control group. This indicates that the loaded particles have a certain protective effect on the liver, with the high-dose group having a more effective effect. A horizontal comparison of the high-dose loaded particle group and the puerarin group revealed that the ALT activity in the high-dose loaded particle group was 43.4 U / L higher than that in the puerarin group, indicating that the edible and medicinal composite particles PHZn-COSH-puerarin can better protect the active ingredients of puerarin, improve its bioavailability, and thus more effectively reduce the damage of alcohol to the liver.

[0127] Effects of different test samples on AST activity in serum of mice with acute alcoholic liver injury Figure 7As shown in Figure B. AST activity in the model control group was significantly elevated, with a statistically significant difference compared to the blank control group (p < 0.05), indicating that alcohol intake caused severe damage to mouse liver cells, leading to the release of AST into the serum. Both silybin and puerarin significantly reduced AST activity, from 117.2 U / L in the model control group to 72.6 U / L and 92.8 U / L, respectively. This suggests that these two compounds have a protective effect against alcoholic liver injury, possibly by alleviating hepatocyte damage and reducing AST release. In the unloaded particle group, AST activity was approximately 97.0 U / L, comparable to that in the puerarin group, indicating that the unloaded particles have a protective effect on the liver, possibly due to COS. In the loaded particle groups, AST activity decreased to 68.2 U / L, 79.4 U / L, and 93.8 U / L in the high-dose, medium-dose, and low-dose groups, respectively, indicating that the loaded particles have a protective effect on the liver. In addition, the AST activity in the high-dose and medium-dose loaded particle groups was significantly lower than that in the puerarin group. This is partly due to the improved bioavailability of puerarin through the loading of the composite particles; on the other hand, it may also be that the COS complexed on the surface of the particles played a liver-protective role. In summary, compared with unloaded puerarin and unloaded puerarin composite particles, the puerarin-loaded medicinal and edible composite particles have a superior ability to reduce serum ALT and AST activities, demonstrating good liver-protective activity.

[0128] Figure 8 Figure A shows the effects of different test samples on ADH activity in liver tissue of mice with acute alcoholic liver injury. Compared to the model control group, silybin, puerarin, and loaded particles all demonstrated enhanced ADH activity, but with varying effects. The enhanced effect of loaded particles at high doses was most significant, indicating that loading can more effectively protect the active ingredient of puerarin and enhance its utilization efficiency in the body, thereby more effectively maintaining ADH activity levels in the liver. This also demonstrates the potential of loaded particles in improving alcoholic liver injury.

[0129] Effects of different test samples on ALDH activity in liver tissue of mice with acute alcoholic liver injury Figure 8 As shown in Figure B, ALDH activity in the model control group was significantly reduced compared to the blank control group, indicating that the establishment of the acute alcoholic liver injury model inhibited ALDH activity in the liver. Silybin, puerarin, and the loaded particles all increased ALDH activity to varying degrees compared to the model control group, with the high-dose embedded particle group showing the most significant effect. This suggests that the composite particles can effectively alleviate the inhibitory effects of alcoholic liver injury on ALDH activity, accelerate acetaldehyde metabolism, and mitigate acetaldehyde's toxic effects on the liver.

Claims

1. A medicinal and edible composite granule, characterized in that: The particles are phosphorylated zein-chitosan oligosaccharide particles loaded with puerarin, wherein the mass ratio of puerarin, zein and chitosan oligosaccharide is 1:5:2-13.

2. The medicine-food composite granules according to claim 1, characterized in that: The chitosan oligosaccharide is an oligosaccharide with a polymerization degree of 2-20.

3. A method for preparing the medicine-food composite particles according to claim 1, characterized in that the steps include: (1) Add puerarin at a final concentration of 5-15 mg / mL to a 4-6% zein-ethanol solution and mix; (2) adding 0.5-1.5 times the volume of the solution obtained in step 1 with a 0.1-0.5% sodium carbonate-ethanol solution by mass volume fraction and mixing; (3) adding 3-5 times the volume of anti-solvent to the solution obtained in step 2 and mixing; (4) removing ethanol from the solution obtained in step 3 by distillation under reduced pressure, and using an anti-solvent to make up the evaporation volume; (5) adding 3-5 times the volume of 0.1-2 mg / mL sodium tripolyphosphate solution to the solution obtained in step 4 and mixing the mixture; (6) adding chitosan oligosaccharide (0.2-5 times the amount of zein) to the solution obtained in step 5 and mixing; (7) The solution obtained in step 6 is dialyzed and freeze-dried to obtain medicinal and edible composite particles.

4. The preparation method according to claim 3, characterized in that In the zein-ethanol solution in step 1, the ethanol concentration is 60-80%.

5. The preparation method according to claim 3, characterized in that The preparation method of the sodium carbonate-ethanol solution in step 2 is: adding 1.5-4 times the volume of anhydrous ethanol to a sodium carbonate aqueous solution with a mass volume fraction of 1%, and mixing.

6. The preparation method according to claim 3, characterized in that The anti-solvent in step 3 is any one of deionized water, double distilled water, and ultrapure water.

7. The preparation method according to claim 3, characterized in that The reduced pressure distillation in step 4 is performed by heating to 35-40° C. and rotary evaporation.

8. The preparation method according to claim 3, characterized in that The dialysis step in step 7 is performed at 2-8° C. with a molecular weight cut-off of 30-40 kDa MWCO.

9. Use of the medicine-food composite particles according to any one of claims 1 to 2 in the preparation of a medicament for treating alcoholic liver injury.

10. Use of the medicine-food composite particles according to any one of claims 1 to 2 in preparing health food for alleviating alcoholic liver damage.